Pengaruh Model Teams Games Tournaments (TGT) terhadap Motivasi Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas XI SMA Negeri 1 Ujung Padang Kabupaten Simalungun Tahun Pembelajaran 2023/2024 - Lovianna Br Manullang; Robinhot Sihombing; Dame Taruli Simamora; Dorlan Naibaho; Tianggur Medi Napitupulu (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The research aims to determine the positive and significant influence of the Teams Games Tournaments (TGT) Model on Learning Motivation for Christian Religious Education and Character in Class The research hypothesis is that there is a positive and significant influence between the Teams Games Tournaments (TGT) Model on Learning Motivation for Christian Religious Education and Characteristics of Class XI Students of SMA Negeri 1 Ujung Padang, Simalungun Regency, Academic Year 2023/2024. This research is a regression research using Inferential Statistics techniques. The population of all class XI students at SMA Negeri 1 Ujung Padang who are Protestant Christians is 138 people. Random sampling (random sampling) is 30% of the total population, namely 40 people. The research instrument is a closed questionnaire. From the determination coefficient test, the value r2 = 0.555 is obtained. From the determination value (r2), it can be seen that the percentage of influence between the Teams Games Tournaments (TGT) Model on the Learning Motivation of Christian Religious Education and Character of Class XI Students of SMA Negeri 1 Ujung Padang, Simalungun Regency, Academic Year 2023/ 2024 is 55.5%. The results of the analysis requirements obtained values ​​rxy = 0.745> rtable = 0.312 and tcount = 6.896> ttable = 2.024 showing that there is a relationship between the Teams Games Tournaments (TGT) model and Christian Religious Education Learning Motivation and Character Characteristics of Students and obtained a regression equation Ŷ = 19.72 +0.564X. Hypothesis testing obtained Fcount=47.55>Ftable=4.09 so H0 is rejected and Ha is accepted. The research concluded that there was a positive and significant influence of the Teams Games Tournaments (TGT) Model on the Learning Motivation for Christian Religious Education and Character of Class